Evaluating Community Violence Intervention Programs: A Scoping Review Synthesizing Methods and Measures - Meron Girma MPH; Julia Schleimer MPH, PhD; Astrid Aveledo MPA; Ayah Mustafa BA; Camerin Rencken MPH, PhD; Carolyn Thurston MA; Deepika Nehra MD; Kris Torset BA; Kristian Jones MA, PhD; Laura Johnson MSW; Lauren Polansky MLS, MPH; Olivia McCollum MPH; et al. (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Community violence intervention (CVI) is a promising strategy to reduce community violence, but research on CVI programs remains underdeveloped. While prior reviews have examined the effectiveness of certain CVI models, we lack a comprehensive synthesis of how CVI research is done and what measures are used. We conducted a scoping review of CVI evaluation measures and methods in the United States, reviewing both peer-reviewed and gray literature from 1996 through 2023. We summarized characteristics of CVI program evaluations, including evaluation measures used, units of analysis, and involvement of external partners—including community members—in the evaluation. Of 1763 articles screened, 149 were included. A plurality of studies examined both outcome and process measures (38.9%), and use of process measures increased over time. Most outcome evaluations used only deficit-based measures (76.4%), with variation across CVI model/approach. Authors of studies included in this review reported that CVI practitioners contributed to evaluations in various ways, but only 10.7% of evaluations included CVI practitioners as authors. Process measures were most often collected at the individual level (84.2%), while outcome measures were collected relatively equally at the individual (56.6%) and community level (53.8%) though with notable variation across CVI models/approaches. Community partners working in CVI were part of our authorship team and offered critical insights into interpreting the findings from this scoping review. Findings underscore the need for a more comprehensive approach to CVI evaluation. By including process and outcome measures, including community-level units of analysis in addition to the typical individual-level ones, employing asset-based frameworks, and actively involving community voices, future research can more effectively assess the implementation and impacts of CVI programs.